Energy Conversion at Kinetic Scales in the Turbulent Magnetosheath - Vörös, Zoltán; Yordanova, Emiliya; Khotyaintsev, Yuri V.; Varsani, Ali; Narita, Yasuhito (Frontiers in Astronomy and Space Sciences, 2019)
The process of conversion or dissipation of energy in nearly collisionless turbulent space plasma is yet to be fully understood. The existing models offer different energy dissipation mechanisms which are based on wave-particle interactions or nonresonant stochastic heating. There are other mechanisms of irreversible processes in space. For example, turbulence generated coherent structures, e.g. current sheets are ubiquitous in the solar wind and quasi-parallel magnetosheath. Reconnecting current sheets in plasma turbulence are converting magnetic energy to kinetic and thermal energy. It is important to understand how the multiple (reconnecting) current sheets contribute to the spatial distribution of turbulent dissipation. However, detailed studies of such complex structures have been possible mainly via event studies in proper coordinate systems, in which the local inflow/outflow, electric and magnetic field directions and gradients could be studied. Here we statistically investigate different energy exchange/dissipation (EED) measures defined in local magnetic field-aligned coordinates, as well as frame-independent scalars. The presented statistical comparisons based on the unique high-resolution MMS data contribute to a better understanding of the plasma heating problem in turbulent space plasmas.